Dietary fat and calcium level effect on feedlot performance and carcass merit in steers - Bock, B.; Brandt, Robert T., Jr.; Harmon, D.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding fat increased feed intake and average daily gain, but feed efficiency was not affected. Feeding high levels of calcium (.9%) had no overall effect, but may tend to increase intake when fed with diets that contain primarily vegetable fat or highly unsaturated fat products.
Keywords: Beef; Fat; Performance; Carcass Merit; Steers; Calcium